Graph Metical Problems of the Pashto Language Alphabet - Pohanyar Nasratullah Nasrat (Randwick International of Education and Linguistics Science Journal, 2023)
This research article discusses the graph metical problems of the Pashto-language alphabet. That are the issue of the waw(و), force or zawar (ه), zawarky(ۀ) and yaa(ی). The Pashto alphabet has three waw (و) such that grapheme is on. also in this alphabet force (zawar) and zurki there are different sounds but is writhing by on grapheme in Pashto language. Although this problem has been solved at the moment, but it is not observed in writing because of lack of attention the authors. There are also five yaas in Pashto-language alphabet, two of which are the hamzadar yaa (ئ) and other one has the tail yaa(ۍ)its sound is the same, but there are two graphs such as those are used the hamzadar yaa(ئ) in the verb and the tail (ۍ) yaa is using in the noun. There are also issue of the alaf(آ) alaf the himself having the mad (⁓) for example (آبا - àbà) in this word alaf has the mad and other alaf does not have the mad because the first alaf is used at the beginning of the word and make the syllable and other alaf is this word used with be(ب) make the syllable but not having the mad.